Expression optimisation of tobacco etch virus (TEV) proteases. - Low, Marcus Yi Hao. (2010)
Tobacco Etch Virus (TEV) proteases is utilized as a useful reagent for the cleavage of recombinant fusion protein due to its stringent sequence specificity. However the production of TEV protease in E. coli has been hampered by insolubility. To improve the expression level of the target protein, the effects of different expression conditions were systematically investigated in this present report. Several fermentation parameters such as medium composition, expression temperature, induction time and induction concentration were studied for optimized expression. The optimum fermentation condition that gave the highest TEV soluble expression yield were as follows: cultivation at 30oC in LB medium, induction at late stage of exponential growth phase (pre-induction period of 4 hours) with 0.4mM IPTG and a post-induction expression period of 5 hours. Before optimizing, the target protein yield was 5.0 mg/l (soluble fraction) and 5.1 mg/l (insoluble fraction). Under the optimized conditions, the expression yield of the target protein saw an increase by considerably more than twofold for soluble and insoluble protein expression (i.e. 12 mg/l and 12 mg/l, respectively). This improved upstream expression yield will enhance overall process productivity and ease the large scale production of pure TEV protease.